PERAN LEMBAGA PEMASYARAKATAN KELAS II A YOGYAKARTA DALAM PEMBINAAN NARAPIDANA - , Dwi Setyo Wahyudi; , Drs. Djuni Prihatin, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research intent to know Correctional Institution Role Brazes II A Yogyakarta in Prisoner construction. This research is done on year 20Q9 - 2010. This research constitute kualitatifs research (Qualitative Research)with descriptive approaching. Gathered data via interview, observation, and documentation. This observational subject covers 7 lAP AS clerks, 7 Prisoners, 3 Ex prisoners. This observational object is lAP AS builder that do construction in mental and skill area. Analysis did by analysis kualitatifs tech descriptive through data reduction step, data representation, and conclusion pull. Result observationaling to point out that: first, Prisoner construction pattern is pass through three steps, which is first phase maximal security, second phase medium security, minimal phase security. Both of , Prisoners criminological root stemmed on stigma, unemployment problem, family inharmonious, its frail is spiritual's mental, and skil's frail and skill. Third, lAP AS role in Prisoner construction is aspect deep empowerment strengthen spiritual's mental and empowerment in aspect strengthens skil Prisoner skill. In conclusion, lAPAS has role that adequately is of important deep back Prisoner as society that doesn't deviate.